GEOLOGY AND WATER GEOCHEMISTRY OF BEUNGGA GEOTHERMAL, TANGSE DISTRICT, PIDIE REGENCY, ACEH PROVINCE - Anisa, Aidina
This research was conducted in Beungga and its surrounding area, Tangse Regency, Pidie District, Aceh Province on 95?54’11” – 95?51’0” E dan 5?11’13” – 5?6’14” N around 54 km2 (9 x 6 km2). Geological mapping with the scale of 1:25,000 and geochemistry analysis of geothermal water were done to discover the geological setting and the characteristic of geothermal system in the research area. Geomorphological unit of the research area consists of 5 unit: (1) Beungga Graben Valley Unit, (2) Titeu Homocline Valley Unit, (3) Alue Rabo Folded Hills Unit, (4) Tangse Faults Block Ridge Unit, (5) Seukeuk Faulted Metamophic Hills Unit. Meanwhile, Stratigraphy of the research area consists of 6 units and 1 deposit: (1) Slate Unit, (2) Andesite Unit, (3) Granodiorite Unit, (4) Sandstone Unit, (5) Conglomerate - Sandstone Unit, (6) Siltstone Unit and surface deposit of Alluvial. Geologic structures in this research are 13 strike-slip faults and 3 normal faults controlled by the Sumatran Faults System, also thrust faults and anticline. The forming of units occupied in this research were formed in various ages. Slate and Andesite Units were formed during Late Jurassic – Middle Cretaceous. Granodiorite Unit was intruded Slate Units during Paleocene. Sandstone Unit was formed during Oligosen, Conglomerate - Sandstone and Siltstone Units were formed during Mid-Miocene. Alluvial deposit was sedimented during Recent. The geothermal manifestations of this research area occur at five locations, as hot and warm springs with temperatures of 50°– 82°C and Cl-SO4-HCO3 water type. The research area is interpreted to have two geothermal reservoirs which are Beungga and Alue on faults fractured Slate and Andesite Units. Beungga and Alue reservoirs have respectively fluid temperature of 110 – 130°C at a depth of ±500 meters and 150 – 170°C at a depth of ±750 meters. Both of these reservoirs have 17 MW of hypotetic resources. This research field has geothermal system controlled by the strike-slip faults structure and the forming of pull apart basin.